TEAM-BASED LEARNING AND GENERIC CAPABILITIES IN STUDENTS WITH AND WITHOUT EXPERIENCING THE INDONESIAN QUALIFICATION FRAMEWORK CURRICULUM-BASED: EVIDENCE FROM ACCOUNTING EDUCATION STUDENTS IN INDONESIA - Zainal, Andri; Putri, Wildanin Haurin; Kartika, Venny Tritara; Sriwedari, Tuti (Universitas Negeri Medan, 2020)
Student skills should be able to be trained and developed during the learning process, especially generic skills. The purpose of this study is to analyze the effect of team-based learning on the generic abilities of accounting students at Medan State University. The population in this study were accounting education program students totaling 96 students from class of 2015 and 107 students from class of 2015. Data collection techniques using questionnaires. The validity, reliability, and classic assumption testing are employed before conducting hypothesis testing using a two samples t-test for difference of means. The results showed that there was an effect of the application of the Team-Based Learning (TBL) learning model on generic abilities in Accounting Education students. Keywords: Team Based Learning, Generic Capabilities, Accounting Students, Universitas Negeri Medan.